Apostolic folly: Pauline foolishness discourse in socio-historical context - Punt, Jeremy (Stellenbosch Theological Journal, 2019)
Foolishness discourse is prominent in the Pauline letters, not only because of its statistical prevalence but also because of its centrality to the argumentation in the letters. Paul’s arguments on wisdom and foolishness are mostly done in close proximity to the associated notions of strength and weakness, and together reverberate within the context of the all-pervasive, all-powerful Roman Empire, as both the reflection and distillate of it, as well as the fabricator and promotor of similar notions and values. The focus of this contribution is to understand the importance of Paul’s self-portrayal as fool for the discourse he constructs in 1 Corinthians 1–4, and in particular, for his apostolic self-understanding and the portrayal and presentation of his message within this foolishness discourse.